2018
DOI: 10.1002/maco.201810383
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of localized corrosion of heat treated Er‐ and Zr‐containing A356 alloys in 3.5 wt% NaCl aqueous solution

Abstract: The influences of Er and Zr additions on the corrosion behavior of A356 (Al‐7Si‐0.4Mg) alloy are investigated. Electrochemical tests (potentiodynamic polarization and electrochemical impedance spectroscopy), gravimetric analyses, and microstructural investigations demonstrate that 0.3 wt% Er nominal addition is beneficial for the corrosion resistance of A356 alloy, due to a modified eutectic morphology and a low volume fraction of intermetallic compounds. The further addition of about 0.5 wt% Zr, on the other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
1
4
0
1
Order By: Relevance
“…In general, the potential difference of the intermetallics present in the microstructure of E3 was comparable or lower than that the intermetallic compounds in A356 to the matrix. The reduced electrochemical potential differences measured between the Al matrix and the intermetallic compounds explain the lower tendency for corrosion localization, as observed in Figure and in previous investigations …”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In general, the potential difference of the intermetallics present in the microstructure of E3 was comparable or lower than that the intermetallic compounds in A356 to the matrix. The reduced electrochemical potential differences measured between the Al matrix and the intermetallic compounds explain the lower tendency for corrosion localization, as observed in Figure and in previous investigations …”
Section: Resultssupporting
confidence: 83%
“…It is evident that Zr‐enrichment in the measured chemical composition of the intermetallic compounds increased the potential difference with respect to the Al matrix and this could be suggested as the cause of the reduced corrosion resistance of EZ35 emerged in Colombo et al…”
Section: Resultsmentioning
confidence: 99%
“…The effect of the corrosion resistance of Er and Zr on an A-356 alloy obtained by permanent metal mold was studied by Colombo et al [13]. By performing immersion corrosion tests, they observed that the addition of Er decreased the corrosion rate from 45.8 µg/cm 2 d to 4.2 µg/cm 2 d and they associated this improvement with the modification of the morphology of eutectic silicon from The corrosion resistance of an AlSi5Cu1Mg alloy with different La additions (0.3%, 0.6%, and 0.9%) was examined [12].…”
Section: Influence Of Addition Of Rare Earths On Corrosion Resistancementioning
confidence: 99%
“…The effect of the corrosion resistance of Er and Zr on an A-356 alloy obtained by permanent metal mold was studied by Colombo et al [13]. By performing immersion corrosion tests, they…”
Section: Corrosion Resistance Of Coatings Obtained By Different Surfamentioning
confidence: 99%
“…Recently, research on A356 is focused on performance improvements via multi-element microalloying and the subsequent heat treatment processes [4][5][6][7][8]. Meanwhile, rare earth elements, such as erbium, lanthanum, scandium, cerium, and europium, have been studied extensively [9][10][11][12][13]. These elements are chemically very active, and by doping them into the aluminum alloy, alloy purification, degass-ing, grain refinements, and mitigation of harmful effects from impurities could be achieved.…”
Section: Introductionmentioning
confidence: 99%